Long-term Exposure to Outdoor and Household Air Pollution and Blood Pressure in the Prospective Urban and Rural Epidemiological (PURE) Study - Arku, Raphael E (Environ Pollut, 2020)
Exposure to air pollution has been linked to elevated blood pressure (BP) and hypertension, but most research has focused on short-term (hours, days, or months) exposures at relatively low concentrations. We examined the associations between long-term (a 3-year average) concentrations of outdoor PM(2.5) and household air pollution (HAP) from cooking with solid fuels with BP and hypertension in the Prospective Urban and Rural Epidemiology (PURE) study. Outdoor PM(2.5) exposures were estimated at year of enrollment for 137,809 adults aged 35-70 years from 640 urban and rural communities in 21 countries using satellite and ground-based methods. Primary use of solid fuel for cooking was used as an indicator of HAP exposure, with analyses restricted to rural participants (n= 43,313) in 27 study centers in 10 countries. BP was measured following a standardized procedure and associations with air pollution examined with mixed-effect regression models, after adjustment for a comprehensive set of potential confounding factors. Baseline outdoor PM(2.5) exposure ranged from 3 to 97 μg/m(3) across study communities and was associated with an increased odds ratio (OR) of 1.04 (95% CI: 1.01, 1.07) for hypertension, per 10 μg/m(3) increase in PM(2.5). This association demonstrated non-linearity and was strongest for the fourth (PM(2.5) > 62 μg/m(3)) compared to the first (PM(2.5) < 14 μg/m(3)) quartiles (OR=1.36, 95% CI: 1.10, 1.69). Similar non-linear patterns were observed for SBP (β=2.15, 95% CI: −0.59, 4.89), DBP (β=1.35, 95% CI: −0.20, 2.89) while there was no overall increase in ORs across the full exposure distribution. Individuals who used solid fuels for cooking had lower BP measures compared to clean fuel users (e.g. 34% of solid fuels users compared to 42% of clean fuel users had hypertension), and even in fully adjusted models had slightly decreased odds of hypertension (OR = 0.93; 95% CI: 0.88, 0.99) and reductions in systolic (−0.51 mmHg; 95% CI: −0.99, −0.03) and diastolic (−0.46 mmHg; 95% CI: −0.75, −0.18) BP. In this large international multi-center study, chronic exposures to outdoor PM(2.5) was associated with increased BP and hypertension while there were small inverse associations with HAP.